Architectural Review Of Indonesian National Gallery Building - Yoga Satya; Vina Nihayatul Maziyah; Salmon Priaji Martana (Program Studi Arsitektur Fakultas Sains dan Teknik (F-INTEN), 2022)
The gallery building is a unique function building whose design must be handled carefully because it involves many aspects related to the physical artifacts, user activities, and values. The application will become more complicated if the gallery is not developed from the beginning but develops an existing building and already has a strong character before. The Indonesia National Gallery Building is one interesting case, set from an old heritage building. The functions of a modern gallery and its accessories must be adapted to the building's initial character of classical architecture. The purpose of this research is to make a functional study of the gallery building, especially at the National Gallery of Indonesia (GNI), and to prepare spatial design rules for facilities that do not yet exist, both in terms of area for managers and exhibition rooms. The architectural survey method aims to overview the advantages and disadvantages of the Indonesia National Gallery building for improvement in another case of designs.